Effect of Occupational Therapy Home Program on Activities of Daily Living of 5-12 Years Old Children - Sara Afshar; Mehdi Rassafiani; Seyyed Ali Hosseini (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: Cerebral palsy is one of the most common causes of physical disability in childhood that leads to various difficulties and reduces the level of independence and participation in activities of daily living. The aim of this study was to investigate the effects of Occupational Therapy Home Program on activities of daily living of 5-12 year-old children. Materials & Methods: In this clinical trial, 48 children were selected and randomly divided into the intervention and control groups. Common practices of occupational therapy were applied for a period of 4 months for both groups. In addition, the intervention group received the Occupational Therapy Home Program in the form of workshops and educational pamphlets with telephone follow-ups. The Activities Scale for Kids (ASK) was used to assess activities of daily living, and independent t-test, chi-square test, Fisher exact test and covariance analysis were used to analyze the results. Results: There was significant difference in activities of daily living between the two groups (P=0.001). There were significant differences in all subtests of the activities of daily living (P0.05). Conclusion: Occupational Therapy Home Program increased activities of daily living of children with cerebral palsy and can be considered useful in addition to common occupational therapy programs.